Pengelolaan Media Pembelajaran di tingkat MI/SD - Fajriwasti, Yossi; Lestari, Suci Indah; Alfarisi, Salman; Sunarti, Sunarti (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
The management of learning media at the elementary school level is one of the supports for achieving the targeted learning outcomes. Media management is our way as educators/teachers to manage something that we will achieve in a program for providing learning media at the elementary school level. This research is a literature study that analyzes several sources, both books, journals, and other references to draw a conclusion as a result of the discussion. For this reason, it was found that there are four stages of learning media management, namely, media planning, media organization, media implementation, and media evaluation. Of the four, it is the management or management of media and learning resources at the MI and SD levels. With the management of learning media, the learning process will run smoothly and effectively.